Team approach to polypharmacy evaluation and reduction: feasibility randomized trial of a structured clinical pathway to reduce polypharmacy - Dee Mangin; Larkin Lamarche; Gina Agarwal; Abbas Ali; Alan Cassels; Kiska Colwill; Lisa Dolovich; Naomi Dore Brown; Barbara Farrell; Karla Freeman; Kristina Frizzle; Scott R. Garrison; et al. (Pilot and Feasibility Studies, 2023)
Abstract Background Polypharmacy is associated with poorer health outcomes in older adults. Other than the associated multimorbidity, factors contributing to this association could include medication adverse effects and interactions, difficulties in managing complicated medication regimes, and reduced medication adherence. It is unknown how reversible these negative associations may be if polypharmacy is reduced. The purpose of this study was to determine the feasibility of implementing an operationalized clinical pathway aimed to reduce polypharmacy in primary care and to pilot measurement tools suitable for assessing change in health outcomes in a larger randomized controlled trial (RCT). Methods We randomized consenting patients ≥ 70 years old on ≥ 5 long-term medications into intervention or control groups. We collected baseline demographic information and research outcome measures at baseline and 6 months. We assessed four categories of feasibility outcomes: process, resource, management, and scientific. The intervention group received TAPER (team approach to polypharmacy evaluation and reduction), a clinical pathway for reducing polypharmacy using “pause and monitor” drug holiday approach. TAPER integrates patients’ goals, priorities, and preferences with an evidence-based “machine screen” to identify potentially problematic medications and support a tapering and monitoring process, all supported by a web-based system, TaperMD. Patients met with a clinical pharmacist and then with their family physician to finalize a plan for optimization of medications using TaperMD. The control group received usual care and were offered TAPER after follow-up at 6 months. Results All 9 criteria for feasibility were met across the 4 feasibility outcome domains. Of 85 patients screened for eligibility, 39 eligible patients were recruited and randomized; two were excluded post hoc for not meeting the age requirement. Withdrawals (2) and losses to follow-up (3) were small and evenly distributed between arms. Areas for intervention and research process improvement were identified. In general, outcome measures performed well and appeared suitable for assessing change in a larger RCT. Conclusions Results from this feasibility study indicate that TAPER as a clinical pathway is feasible to implement in a primary care team setting and in an RCT research framework. Outcome trends suggest effectiveness. A large-scale RCT will be conducted to investigate the effectiveness of TAPER on reducing polypharmacy and improving health outcomes. Trial registration clinicaltrials.gov NCT02562352 , Registered September 29, 2015.